BRAVOSEIS: Geophysical investigation of rifting and volcanism in the Bransfield strait, Antarctica. (December 2020) - Almendros, J.; Wilcock, W.; Soule, D.; Teixidó, T.; Vizcaíno, L.; Ardanaz, O.; Granja-Bruña, J.L.; Martín-Jiménez, D.; Yuan, X.; Heit, B.; Schmidt-Aursch, M.C.; Geissler, W.; et al.
Abstract: The Bransfield Basin is a back-arc basin located in Western Antarctica between the South Shetland Islands and Antarctic Peninsula. Although the subduction of the Phoenix plate under the South Shetland block has ceased, extension continues through a combination of slab rollback and transtensional motions between the Scotia and Antarctic plates. This process has created a continental rift in the basin, interleaved with volcanic islands and seamounts, which may be near the transition from rifting to seafloor spreading. In the framework of the BRAVOSEIS project (2017–2020), we deployed a dense amphibious seismic network in the Bransfield Strait comprising 15 land stations and 24 ocean-bottom seismometers, as well as a network of 6 moored hydrophones; and acquired marine geophysics data including multibeam bathymetry, sub-bottom profiler, gravity & magnetics, multi-channel seismics, and seismic refraction data. The experiment has collected a unique, high quality, and multifaceted geophysical data set in the Central Bransfield Basin, with a special focus on Orca and Humpback seamounts. Preliminary results confirm that the Bransfield region has slab-related intermediate depth seismicity, with earthquake characteristics suggesting distributed extension across the rift. Gravity and magnetic highs delineate a segmented rift with along-axis variations that are consistent with increased accumulated strain to the northeast. Orca volcano shows evidences of an active caldera and magma accumulation at shallow depths, while Humpback volcano has evolved past the caldera stage and is currently dominated by rifting structures. These differences suggest that volcanic evolution is influenced by the position along the rift. Although a lot of analysis remains, these results provide useful constraints on the structure and dynamics of the Bransfield rift and associated volcanoes.